FDI and the Investment Climate in the CIS Countries - Shiells, Clinton (IMF Policy Discussion Papers; Policy Discussion Paper, 2003)
In view of disappointing levels of inward foreign direct investment (FDI), this paper examines capital flows into the Commonwealth of Independent States (CIS) countries and investigates the main impediments to a more favorable investment climate. Direct investment inflows have generally been related to natural resource extraction or energy transportation infrastructure projects, large privatization transactions, and debt/equity swaps to pay for energy supplies. Low FDI inflows despite strengthening macroeconomic performance has reflected a weak investment climate particularly owing to incomplete structural reforms. IMF staff working on the countries concerned cited burdensome tax systems, widespread corruption, extensive state intervention coupled with weak legal and regulatory frameworks, and incomplete structural reforms as the main impediments.